WYKŁAD JAKO PERFORMANS. PERFORMANS JAKO WYKŁAD. PERFORMATYWNE WYMIARY PRAKTYKI BADAWCZEJ - Bielecka-Prus, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
A lecture as a genre can be analyzed as a ritual form of performance with its interactional order. A traditional lecture is a regulated speech act and the body of a researcher is not an essential carrier of meanings. Multimedia presentations change a role of researcher’s body but only the postmodern turn and new paradigm in ethnography treats the body as an integral part of the research process. The first part of the article focuses on the main features of the academic lecture as a discursive genre. In the second part of the text, methodological assumptions of performative ethnography will be discussed together with its main functions and criteria for evaluation.